(untitled) (Prostor, 2024)
The former tobacco industry complexes in Dalmatia and Herzegovina have multiple values ​​and represent a significant spatial resource. This is insufficiently recognized and they mostly fall into disrepair due to neglect and disuse. In order to contribute to their preservation, renewal and reuse, the doctoral dissertation is focused on determining their identity factors, evaluation criteria and criteria for renewal and revitalization interventions.